MicroRNA-155 Targets SMAD2 and Modulates the Response of Macrophages to Transforming Growth Factor-β - Louafi, Fethi (American Society for Biochemistry and Molecular Biology, 2010)
Transforming growth factor-beta (TGF-β) is a pleiotropic cytokine with important effects on processes such as fibrosis, angiogenesis, and immunosupression. Using bioinformatics, we identified SMAD2, one of the mediators of TGF-β signaling, as a predicted target for a microRNA, microRNA-155 (miR-155). MicroRNAs are a class of small non-coding RNAs that have emerged as an important class of gene expression regulators. miR-155 has been found to be involved in the regulation of the immune response in myeloid cells. Here, we provide direct evidence of binding of miR-155 to a predicted binding site and the ability of miR-155 to repress SMAD2 protein expression. We employed a lentivirally transduced monocyte cell line (THP1–155) containing an inducible miR-155 transgene to show that endogenous levels of SMAD2 protein were decreased after sustained overexpression of miR-155. This decrease in SMAD2 led to a reduction in both TGF-β-induced SMAD-2 phosphorylation and SMAD-2-dependent activation of the expression of the CAGA(12)LUC reporter plasmid. Overexpression of miR-155 altered the cellular responses to TGF-β by changing the expression of a set of genes that is involved in inflammation, fibrosis, and angiogenesis. Our study provides firm evidence of a role for miR-155 in directly repressing SMAD2 expression, and our results demonstrate the relevance of one of the two predicted target sites in SMAD2 3′-UTR. Altogether, our data uncover an important role for miR-155 in modulating the cellular response to TGF-β with possible implications in several human diseases where homeostasis of TGF-β might be altered.